PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS NASABAH (Studi pada Bank BNI Syariah Kantor Cabang Pekanbaru) - Yelli Trisusanti; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the effect of service quality and trust on customer loyalty at Bank BNI Syariah Branch Office Pekanbaru partially and simultaneously. This study used questionnaire as a data gathering tool distributed to 100 customers of Bank BNI Syariah branch office Pekanbaru. The questionnaire data is then processed using descriptive analysis and statistical analysis using SPPS 17,0 by performing validity test, reliability test, linear linear analysis, multiple linear analysis, determinant analysis (R2) and hypothesis test with t test (partial) and f test (Simultaneous).The results showed that the results of the first variable hypothesis testing is the quality of service is t count (14,762) > t table (1,984), means that service quality variables significantly influence customer loyalty. The second variable is trust that is t count (13,928) > t table (1,984) means trust variable have significant effect to customer loyalty. The result of F test of service quality and trust is F count (191,603) > F table (3,090), means that the quality of service and trust simultaneously influence significantly to customer loyalty.Keywords: Service Quality, Trust, Customer Loyalty